论建国初期翻译工作的组织化和计划化 —— 以“第一届翻译工作会议”及对其文学翻译的影响为中心 = On the organization and planning of the translation activities in the People’s Republic of China in the early 1950s : using "The First National Conference of Translation" as an example - 崔峰 Cui Feng (复旦大学出版社 Fudan University Press, 2019)
China was firmly griped by communist ideology from the founding of the People’s Republic of China on October 1, 1949 to the eve of the Cultural Revolution in 1966. With the communist ideology looming large in the background, literary translation during this period was greatly influenced by factors such as China’s alliance with the USSR, its friendship with the Eastern European communist countries, its antagonism with the Western capitalist camp, and its literary policy demanding that literature should shape and reflect the revolutionary spirit. How did the unique translation phenomena in China take place? Why did communist party hurry to take the organization and planning of the translation activities into its own hand as soon as the PRC was founded? What was its implication? This essay attempts to answer these questions by taking the 1951 First National Conference of Translation, a key conference manipulated by the communist government and proved influential to the translation activities in the 1950s and the 1960s, as an example.